Multi variate Approach to Define the Quality of Rice - Nandini P V (Department of Home Science, College of Agriculture, 1995)
A study on “ a multi variate approach to define the quality of rice” was carried out assets the major quality parameters such as physical characteristics, cooking characteristics, organoleptic qualities and nutritional composition. Sixty rice varieties (thirty hybrid derivatives, twenty eight traditional / local varieties and two other improved / market varieties ) were selected.